Agricultural Information Needs and their Fulfillment as Perceived by the Farmers in Changing Agricultural Scenario in Maharashtra - Awatade Sudarshan Chandrakant , Souvik Ghosh and R B Singandhupe (Indian Journal of Extension Education, 2017)
Nowadays, there are numerous extension agencies that are providing agricultural extension services to the farmers in theform of information and service support but the results are still not satisfactory in accordance with need fulfillment offarmers in the context of changing agricultural scenario in Maharashtra state. Hence, present study was aimed to assessdiverse information needs of farmers from agricultural extension system. It was conducted in Yavatmal district ofMaharashtra that included a random sample of 80 farmers, 20 each from four randomly selected villages representing twoblocks. The present study reveals that soil, weather and climate, nutrient management, market prices and incomegenerating activities are the prime needed aspects related to agricultural inputs with mean need perception score more than3.5 on four point continuum scale followed by livelihood diversification, agricultural marketing, seeds, agrientrepreneurship, subsidies, plant protection material, weed management, pest and disease management and cropdiversification had mean need perception score more than average (>2.5) on four point continuum scale. However, themost of the information needs were fulfilled partially as opined by the farmers. The low perception of felt needs of thefarmers on post harvest management and higher need perception on marketing aspects clearly indicated the fact ofunwillingness and ignorance on value addition, quality control, etc. of agricultural produce and preference of marketingthe produce as quickly as possible. However, the farmers expressed their interest in capacity building aspects viz.diversification of livelihood, agri- entrepreneurship and crop diversification by growing high value crops.